Psychological-pedagogical problems and prospects of distance learning of students during the Covid-19 pandemics - George Abuselidze; Inna Radzivilova; Olga Mohylevska (E3S Web of Conferences, 2021)
The article analyses the psychological and pedagogical problems and prospects of the distance learning of students during the pandemic period. Studies have shown that the learning process during the quarantine in the spring of 2020 was stressful for all participants in the educational process. This was caused by the lack of previous experience of distance learning and the response from the government and the number of educational problems. It is proved that the problem of insufficient universal access to the internet and the equipment necessary for training has affected both teachers and students. The current situation shows that some teachers working at higher education institutions replaced remote classes with the form of written works, which led to excessive workload of students. Such methods do not contribute to the quality of material assimilation, but on the contrary, create additional stress. It is proved that computerization affects all spheres of human activity and is an important factor in changing the quality of society life. The authors note that in order to ensure the development of higher distance education, it is necessary to improve the regulatory framework in the field of higher distance education, create a computer infrastructure, prepare software for the introduction of electronic educational platforms, as well as train and retrain teachers for conducting distance education courses. It is noted that during the process remote technologies, teachers use various forms of work with students. In particular, including Zoom classes, Skype classes, web classes, where students independently study an educational resource, perform tasks and the teacher checks it and gives a mandatory review of the completed task. The algorithm for assessing the quality of distance learning systems is justified and the use of an integral indicator with weighting coefficients is proposed, which allows us to quantify the value of local quality indicators and complex quality characteristics of distance learning systems.
Keywords: I21; I23; I24; I25; D83; D91; 330; Analysis of Education; Higher Education; Education and Inequality; Education and Economic Development; Distance Learning; COVID-19